Tipos de tutorados y su influencia en las características agronómicas y rendimiento de Cucumis sativus L. var. “pepino regional”, en Zungarococha-Loreto.2021 - Jugo Davila, Fatima Marissa (2022)
The experiment "types of tutors and their influence on the agronomic characteristics and yield of Cucumis sativus L. var. " regional cucumber", in Zungarococha-Loreto.2021", was held at the facilities of the Workshop on Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located south of the city of Iquitos. The type of research was experimental, explanatory with an independent variable (Types of tutors) and eight dependent variables (plant height, fruit length, fruit diameter, number of fruits/plant, fruit weight, fruit weight/plant, fruit weight/plot and fruit weight/ha. the objective of the research work was to determine the influence of types of tutors on the agronomic characteristics and yield of Cucumis sativus L. var. "regional cucumber", in Zungarococha-Loreto.2021. The experimental design that was used was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 2 rows, 5 plants/row and the sampling unit consisted of four plants/experimental unit. At the end of the experiment we had the following conclusions: There are statistical differences in the variables plant height, fruit weight, fruit weight/plant, fruit weight/ha; there are no statistical differences in the sources of long fruit variation, fruit diameter and number of fruits/plant; the T4 Treatment (vine type), presented the highest average value of fruit weight, with 712 g, the T4 Treatment (vine type), presented the highest average value of weight of fruits / plant, with 2,848.25 g; treatment T4 (vine type), presented the highest average value of weight of fruits / ha, with 17.09 t; the T4 Treatment (vine type), presented the best Benefit/Cost ratio, obtaining a utility of S/.19,230.00.